2008
DOI: 10.1093/eurheartj/ehn465
|View full text |Cite
|
Sign up to set email alerts
|

CETP genotype predicts increased mortality in statin-treated men with proven cardiovascular disease: an adverse pharmacogenetic interaction

Abstract: In statin-treated male CAD patients, genetic variation conferring low CETP levels is associated with increased 10-year mortality. This suggests that efficacy of statin therapy to reduce cardiovascular risk depends on CETP genotype and associated CETP plasma levels. This effect may need consideration when administering CETP inhibition to CAD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(46 citation statements)
references
References 35 publications
5
41
0
Order By: Relevance
“…Nevertheless, according to our results, taking lipid-lowering drugs does not modify the association between CETP genotypes and HDL-C concentrations in this high cardiovascular risk Mediterranean population and does not have any infl uence on the interaction between CETP genotypes and lifestyle variables. However, there is a study that has found an adverse pharmacogenetic interaction between the CETP genotype and statins with cardiovascular mortality ( 49 ), but this particular issue does not form part of our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, according to our results, taking lipid-lowering drugs does not modify the association between CETP genotypes and HDL-C concentrations in this high cardiovascular risk Mediterranean population and does not have any infl uence on the interaction between CETP genotypes and lifestyle variables. However, there is a study that has found an adverse pharmacogenetic interaction between the CETP genotype and statins with cardiovascular mortality ( 49 ), but this particular issue does not form part of our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the results of REGRESS (Regression Growth Evaluation Statin Study), which is the first study where a possible pharmacogenetic interaction between CETP polymorphisms and statin treatment is mentioned [19], showed significantly higher 10-year mortality in male patients under statins, who were carriers of B2 allele compared to those with B1B1 genotype [20].…”
Section: Statins Are Generally Well Tolerated Medications Their Mainmentioning
confidence: 99%
“…Besides, drugs such as pravastatin and rotuvastatin are not susceptible to CYP inhibition, but are substrates of the a hepatic transporter and solute organic anion-transporting polypeptide (OATP) 1B1 (encoded by the SLCO1B1 gene) which is responsible for liver transportation of the statins 154 . Variants of the apolipoprotein, particularly the apo E and apo A5 also have their share in these processes [155][156][157][158] . Similarly, genetically impaired ABCG2 transporter efflux activity results in a marked increase in systemic exposure to various statins 159 .…”
Section: Genetics and Drug Therapy Of Coronary Artery Diseasementioning
confidence: 99%